World Development Report 2009: A Practical Economic Geography - Deichmann, Uwe; Gill, Indermit; Goh, Chor Ching (2012)
The World Development Report 2009: Reshaping Economic Geography (WDR 2009) was written to inform policy debates about urbanization, lagging areas, and globalization. During almost two years of consultations and dissemination, the report met with broad acceptance among government officials, development professionals, and researchers. Policymakers grappling with difficult spatial development issues have found the report's analytical framework compelling and its policy guidance useful. An exception to this generally favorable reception has been the reaction from a number of economic geographers. In this article, we respond to criticisms about the report's scope, guiding framework, and policy implications that are emphasized in the accompanying articles in this issue of Economic Geography. In conclusion, we agree with economic geographers such as Rodriguez-Pose who call for critical engagement with the report and with the more detailed follow-up studies that use the WDR 2009's framework. This would both improve the quality of spatial policy advice and increase the visibility of economic geographers in international development debates.